2016
DOI: 10.1038/srep37279
|View full text |Cite
|
Sign up to set email alerts
|

Continuous exposure to non-lethal doses of sodium iodate induces retinal pigment epithelial cell dysfunction

Abstract: Age-related macular degeneration (AMD), characterized by progressive degeneration of retinal pigment epithelium (RPE), is the major cause of irreversible blindness and visual impairment in elderly population. We previously established a RPE degeneration model using an acute high dose sodium iodate to induce oxidative stress. Here we report findings on a prolonged treatment of low doses of sodium iodate on human RPE cells (ARPE-19). RPE cells were treated continuously with low doses (2–10 mM) of sodium iodate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…5). We have previously demonstrated that phagocytosed beads would show yellow fluorescence signal and those not phagocytosed would be in green signal 22 . After 5-day nicotine and cotinine treatment, the phagocytotic activity of rat RPE cells on rat POS was significantly reduced in 1 μM nicotine (46.43% phagocytosed beads; p  < 0.001), 1 μM cotinine (62.59% phagocytosed beads; p  < 0.001), 2 μM cotinine (67.09% phagocytosed beads; p  < 0.001) and 2 μM nicotine-cotinine treatments (69.23% phagocytosed beads; p  < 0.01), compared to the vehicle control (92.18% phagocytosed beads).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…5). We have previously demonstrated that phagocytosed beads would show yellow fluorescence signal and those not phagocytosed would be in green signal 22 . After 5-day nicotine and cotinine treatment, the phagocytotic activity of rat RPE cells on rat POS was significantly reduced in 1 μM nicotine (46.43% phagocytosed beads; p  < 0.001), 1 μM cotinine (62.59% phagocytosed beads; p  < 0.001), 2 μM cotinine (67.09% phagocytosed beads; p  < 0.001) and 2 μM nicotine-cotinine treatments (69.23% phagocytosed beads; p  < 0.01), compared to the vehicle control (92.18% phagocytosed beads).…”
Section: Resultsmentioning
confidence: 98%
“…RPE explant culture was used to evaluate the phagocytotic activity of RPE cells ex vivo 22 . Briefly, Sprague Dawley (SD) rats, aged 6–8 weeks, were enucleated and dissected.…”
Section: Methodsmentioning
confidence: 99%
“…19,41 Recent studies in cell cultures of ARPE-19 further show that exposure to sublethal doses of SI retard RPE cell migration and cause reduced expression of the cell junction protein ZO-1. 42 Taken together, these processes probably underlie the rapid formation of retinal edema following SI administration as detected by OCT and histology. The formation and resolution of such edema caused by the early toxicity of SI may explain the observed initial OKT loss followed by partial recovery at 1 week.…”
Section: Discussionmentioning
confidence: 99%
“…Besides using amyloid beta 1-40 oligomers, oxidative stress upon RPE cells may also resemble AMD conditions in vitro. Studies showed that a low dose of sodium iodate significantly decreased phagocytotic activity, cellular acidity, and autophagy, leading to RPE cell degeneration [ 54 , 55 ], while a high dosage of sodium iodate increased the expression of pentraxin 3, thereby accelerating RPE cell death [ 56 ]. Another in vitro model was the application of tert -butyl hydroperoxide on human fetal RPE and APRE-19 cells [ 57 ].…”
Section: Disease Mechanisms Of Amdmentioning
confidence: 99%